2007
DOI: 10.4028/www.scientific.net/ddf.261-262.37
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and doping effect of Ni and Co in the kink on the edge dislocation of bcc iron

Abstract: Using the first-principles self-consistent discrete variational method based upon density functional theory, we investigated the energetics and the electronic structure of the 3d impurities Ni and Co in a kink on the [100](010) edge dislocation (ED) in bcc iron. The calculated results show that the interatomic energies between the impurity atom and the neighboring host atoms decrease. The bonding for the impurity atom (Ni, Co) and the neighboring host Fe atoms is weaker than that for an Fe atom at the X site a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…When a kink pair meets hydrogen during expanding, the sideward motion of the kink pair is impeded by hydrogen (SSH). However, to our knowledge, there exist few studies [20][21][22][23] in literature on the impurity-kink complex based on first-principles method, while the electronic structure of solute impurity atoms within the kink may play an important role in impurity-kink interactions. In the present study, the attempt of first-principles study on impurity (C and N)-kink interaction in bcc Fe is made.…”
Section: Using the First-principles Self-consistent Discrete Variatiomentioning
confidence: 99%
“…When a kink pair meets hydrogen during expanding, the sideward motion of the kink pair is impeded by hydrogen (SSH). However, to our knowledge, there exist few studies [20][21][22][23] in literature on the impurity-kink complex based on first-principles method, while the electronic structure of solute impurity atoms within the kink may play an important role in impurity-kink interactions. In the present study, the attempt of first-principles study on impurity (C and N)-kink interaction in bcc Fe is made.…”
Section: Using the First-principles Self-consistent Discrete Variatiomentioning
confidence: 99%
“…We studied the electronic effects of B, S, Ni and Co impurities on the kink in the [100](010) edge dislocation (ED) of bcc iron [10][11][12] . The calculated results show that boron in the kink can enhance the interatomic interaction between the impurity atom and the neighboring Fe atoms due to the hybridization of B 2p-Fe 3d4s4p orbitals, which impels the migration of kink and leads to a strong pinning effect on the dislocation (hardening).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, although the electronic structure of solute impurity atoms within the kink may play an important role in impurity-kink interaction, little work has been done, to investigate the impurity-kink complex, based upon the first-principles method. We studied the electronic effects of B, Ni and Co impurities upon the kink in the [100](010) ED of bcc iron [13,14]. It is found that boron in the kink can enhance the interaction between the impurity atom and the neighboring Fe atoms, due to the hybridization of B 2p-Fe 3d4s4p orbitals.…”
Section: Introductionmentioning
confidence: 99%